New and little known Coptotriche and Tischeria species (Lepidoptera: Tischeriidae) from Primorskiy Kray, Russian Far East - Stonis, Jonas R.; Diškus, Arūnas; Rocienė, Agnė; Sruoga, Virginijus; Davis, Donald R. (Zootaxa, 2014)
The paper provides data on two new and two little known Coptotriche Walsingham and Tischeria Zeller species from Primorskiy Kray (=Primorskiy Territory), Russian Far East: Coptotriche minuta Diškus & Stonis, sp. nov., Tischeria unca Diškus & Stonis, sp. nov. are described, T. decidua siorkionla Kozlov and T. sichotensis Ermolaev are redescribed. Currently, together with the described new species, the fauna of Tischeridae of Far Eastern Russia comprises three Coptotriche species and seven Tischeria species. A neotype, replacing the missing type series of T. sichotensis, is designated here. For the first time all four species treated from Russian Far East are illustrated with photographs of the adults and genitalia (T. sichotensis also with photographs of the leaf-mines).